Kiprah Ulama Perempuan Nyai Hj. Makkiyah As’ad dalam Membentengi Moralitas Umat di Pamekasan Madura - Mohammad Takdir (Institut Ilmu Keislaman Annuqayah, 2015)
The term ulama>’ is identical to having men characteristics. It is undeniable that during the history of Islam, there were many women ulama>’ with their great contributions on the islamic magnicience and missionaries in the mids of behavioral decadence. In Indonesia, a little attention was given to women ulama>’, while the islamic boarding school (pesantren) has played important role to create them in terms of social empowerment. This study is aimed to address a bibliographical significance of an older woman, or what Javanese popularly known, ‘Nyai’ Makkiah As’ad from Pamekasan, Madura. This study attemps to explore critical contributions of Nyai Makkiah As’ad as moral guider around the pesantrens in Pamekasan. It has been concluded that Nyai Makkiah As’ad mets preconditional requirements of being called ‘ulama’, including having religious capacity to be a professional Muslim proselytizer, having social sense of belonging in the mids of heterogeneous people, having a moral sense of adaptivity in dealing with many social issues, having leadership character to be a prominent figure in some pesantrens in Pamekasan, and having an ulama’ linkage genealogy as daughter of Nahdlatul Ulama leader, Kyai As’ad Syamsul Arifin, with spreadly high influence in Java.